Hot-fusion biodegradable filter support body and air filter composite filter material comprising same

By using a polyester biological degradation of thermal adhesion composite fiber, a dry method non -woven non -woven thermal melt biodegradable filter support body, solving the problem of unable to biodegradation in the existing technology, realizes abandonment The environmental protection effect of the later biodegradation, while meeting the physical requirements of the filter support body.

CN119365247APending Publication Date: 2025-01-24NAM YANG NON WOVEN FABRIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380042112.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-10-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing air filter support cannot biodegrade after being discarded, resulting in environmental pollution and is difficult to meet the physical properties requirements of the filter support.

Method used

The supporting body of the hot -melt biodegraded filter made from a single layer or multi -layer dry method without woven fabrics. Composite fiber composition, a layer of stacking structure is formed through hot melt binding.

Benefits of technology

While meeting the requirements of the filter support body thickness, breathableness, tensile strength and other physicality requirements, it is degraded by biology under soil landfilling conditions after abandonment, thereby reducing environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365247A_ABST
    Figure CN119365247A_ABST
Patent Text Reader

Abstract

The present invention relates to a heat-fusion biodegradable filter support and a composite filter material for an air filter using the same, and more particularly, to an environmentally friendly dry nonwoven fabric heat-fusion biodegradable filter support which is biodegradable in soil landfill when discarded after the end of life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat-fused biodegradable filter support body composed of a dry-laid nonwoven fabric, and more particularly to an environmentally friendly heat-fused biodegradable filter support body that is biodegraded in a soil landfill when discarded, and an air filter composite filter material containing the same. Background Art

[0002] Generally, an air filter is a device for filtering dust and impurities. It is a device arranged in the air inlet and outlet passages to allow filtered clean air to flow into the interior for a dust-free and dust-proof environment. With the increasing industrial development and environmental pollution, the demand for such filter devices is increasing.

[0003] Such air filters are classified into filters for air purifiers, car air conditioning filters, air conditioning filters, etc. according to the purpose of use.

[0004] Usually, an air filter is composed of a dust collecting member that performs a filtering function and a filter support body that supports the dust collecting member. In this case, the dust collecting member mainly uses electrostatically treated polypropylene meltblown nonwoven fabric, and the filter support body uses polyester spunbond nonwoven fabric. On the other hand, the polypropylene or polyester used at this time is a synthetic fiber, which cannot be decomposed when placed in nature after use, thus causing environmental problems. Therefore, it must be landfilled underground or burned after use. In this case, the environmental burden caused by air pollution or landfill becomes a major social problem. In addition, from the perspective of recent global environmental protection and resource recycling, it is necessary to reduce the burden on the environment. Therefore, a material that is biodegradable under soil landfill conditions when discarded after use is required.

[0005] With the demand of the times to reduce the burden on the environment, the demand for filters that are biodegradable under soil landfill conditions after use and discarded has also increased. In addition, the demand for environmentally friendly biodegradable filter supports, which are the main part of the filter, has also increased. In addition, such biodegradable filter supports should maintain the physical properties of a filter support when in use, and also need to maintain the characteristics of being biodegradable under soil landfill conditions when discarded after use. Therefore, it is necessary to prepare a dry non-woven thermal fusion biodegradable filter support that is biodegradable under soil landfill conditions when discarded after use, but the research related to this is very limited. Such a biodegradable filter support includes the difficult issue of satisfying both the physical properties and biodegradability of a filter support. Summary of the invention

[0006] Technical issues

[0007] The object of the present invention is to provide an environmentally friendly dry-laid nonwoven thermally fused biodegradable filter support that is biodegradable in a landfill when discarded.

[0008] Technical Solution

[0009] In order to solve the technical problem, the present invention relates to a heat-fused biodegradable filter support for air filter material, which is a dry non-woven fabric formed by a single layer or multiple layers, and the dry non-woven fabric contains polyester biodegradable heat-bonded composite fibers with a fiber length of 38 to 64 mm and a fineness of 6 to 15 de (denier).

[0010] Furthermore, the present invention relates to a composite filter material for an air filter, comprising: the biodegradable filter support; and a dust collecting member arranged on one side of the biodegradable filter support.

[0011] Effects of the Invention

[0012] The biodegradable filter support of the present invention has sufficient physical properties such as thickness, air permeability, and tensile strength to function as a filter support, and is biodegraded under landfill conditions when discarded after its life as a filter support, thereby reducing the burden on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The present invention is a flowchart of a process for preparing a dry-laid nonwoven thermally fused biodegradable filter support according to an embodiment of the present invention. DETAILED DESCRIPTION

[0014] In order to fully understand the present invention, preferred embodiments of the present invention are described with reference to the accompanying drawings.

[0015] The embodiments of the present invention may be modified into various forms, and the scope of the present invention should not be construed as being limited to the embodiments described in detail below. The present embodiments are provided only to fully illustrate the present invention to those of ordinary skill in the art to which the present invention belongs. When it is determined that the description of the known functions and structures may unnecessarily confuse the gist of the present invention, the detailed description thereof will be omitted.

[0016] like Figure 1As shown, the dry nonwoven fabric constituting the heat-fused biodegradable filter support of the present invention is prepared by the following process: raw yarns are supplied through a material supplying section 100, the entangled raw yarns supplied from the material supplying section 100 are mixed with each other through a material mixing section, the entangled raw yarns mixed by the material mixing section 200 are separated by a hopper section 300, the raw yarns separated by the hopper section 300 are unfolded to a predetermined thickness by a combing section 400 to form a film form, a single-layer nonwoven fabric layer supplied from the combing section 400 is moved left and right by a web laying section 500 to be stacked into a plurality of layers to form a nonwoven fabric layer of a predetermined thickness, the nonwoven fabric layer supplied from the web laying section 500 is stretched and transferred by a drafting section 600, the nonwoven fabric layer stretched and transferred in the drafting section 600 is bonded by a heat-fusion bonding section 700 using heat and pressure, and the nonwoven fabric bonded by the heat-fusion bonding section 700 is wound by a winding section 800.

[0017] Moreover, the roles and functions of the material supply section 100, material mixing section 200, hopper section 300, combing section 400, web laying section 500, heat fusion bonding section 700 and winding section 800, which are the various structural elements of the preparation process of the dry non-woven fabric suitable for the heat-fused biodegradable filter support body of the present invention or the heat-fused biodegradable filter support body preparation process 10, adopt the known structure that can be used in the preparation of non-woven fabric, especially the combing method, or use it by appropriately deforming it, so its specific description will be omitted.

[0018] The carded nonwoven fabric thinly spreads the short fibers as the material to form a network, and the short fibers can be combined by a physical method of heat and pressure to prepare a dry nonwoven thermal fusion biodegradable filter support. In this case, in order to combine such a thermal fusion nonwoven fabric with a dust collector to effectively use it as a filter support, it is necessary to have good air permeability and excellent morphological stability, thereby realizing a thermal fusion nonwoven fabric with a structure that is good in bending workability.

[0019] To this end, the present invention studies the Figure 1 The raw yarn of the material supply part 100, specifically, the biodegradable thermal bonding fiber with a bi-component structure is studied as the raw yarn for thermal fusion, and the thermal fusion dry-laid non-woven fabric suitable for the biodegradable filter support is realized by calendering thermal fusion in the thermal fusion bonding part 700.

[0020] First, the biodegradable thermal bonding composite fiber will be described.

[0021] The biodegradable thermal bonding composite fiber plays a role in combining adjacent different thermal bonding fibers when heat and pressure are applied. The biodegradable thermal bonding composite fiber can be a low-melting point silk (or low-melting point fiber) or a low-melting (LM, Low Melting) silk, or a known fiber called a non-melting point silk (or non-melting point fiber) because it has no melting point but a softening point. The biodegradable thermal bonding fiber can be used without restriction as a biodegradable polyester component in the thermal bonding component used in known fibers for such purposes. In addition, the core-skin composite fiber in which the thermal bonding component is located in the sheath and the high-melting point polyester is located in the core shows more effective results as a filter support.

[0022] The biodegradable thermal bonding composite fiber can be a fiber formed only by the above-mentioned biodegradable thermal bonding component, or can be a fiber formed by exposing the above-mentioned thermal bonding component on the fiber surface. Preferably, the cross-sectional structure of the biodegradable bonding fiber can be a core-skin type composite fiber. In this case, in the core-skin type composite fiber, the thermal bonding component forms the sheath, and a component with a higher melting point than the thermal bonding component, for example, high melting point polyethylene terephthalate, can form the core. Moreover, such a core-skin type composite fiber in which the low melting point polyester resin as the thermal bonding component is located in the sheath and the high melting point polyester resin is located in the core shows more effective results as a filter support.

[0023] According to a more preferred embodiment, the biodegradable thermal bonding composite fiber is a composite fiber prepared from two biodegradable polyester resins with different melting points, including biodegradable low melting point polyester and biodegradable high melting point PET, preferably including biodegradable low melting point PET and biodegradable high melting point PET. Among them, low melting point and high melting point indicate the relative height of the melting point, which is an expression used to distinguish the two biodegradable polyesters.

[0024] The melting point of the low-melting-point polyester may be 100-180°C, preferably 110-150°C. In this case, if the melting point is less than 100°C, the heat resistance may be reduced, and if the melting point is greater than 180°C, the energy cost may increase during heat fusion.

[0025] Furthermore, the softening point of the low melting point polyester may be 100 to 150°C, preferably, the softening point may be 110 to 130°C.

[0026] As the thermal adhesive component constituting the skin portion, the low-melting point polyester resin can be prepared by lowering the melting point by modifying one or more of the polycarboxylic acids and diols used in its polymerization, or by eliminating the melting point and leaving only the softening point. For example, it can include a biodegradable polyester thermal adhesive resin having a melting point of 100 to 180°C or having no melting point and a softening point of 100 to 150°C.

[0027] For example, the biodegradable polyester thermal adhesive resin is formed by a low melting point polyester resin, and the low melting point polyester resin is formed by the following components: an acid component, which is an aromatic component in the polycarboxylic acid and is composed of terephthalic acid or its ester-forming derivative; and a diol component, which is composed of 2-methyl-1,3-propanediol, 2-methyl-1,3-pentanediol and ethylene glycol. Moreover, the diol component may contain 20 to 50 mol percent of the 2-methyl-1,3-propanediol, 0.1 to 2 mol percent of the 2-methyl-1,3-pentanediol and the remaining amount of ethylene glycol in 100 mol percent. In this case, if the 2-methyl-1,3-propanediol in the 100 mol percent diol component is less than 20 mol percent, there will be a problem of reducing thermal adhesiveness due to the reduction of low melting point performance, and if it is greater than 50 mol percent, there will be a problem of reducing cross-section formation and heat resistance due to excessive low melting point. If the content of 2-methyl-1,3-pentanediol in 100 mol % of the diol component is less than 0.1 mol %, the melt viscosity may drop sharply at high temperature due to the low usage amount. If the content is greater than 2 mol %, the operability of the spinning process may be reduced.

[0028] The biodegradable polyester thermal adhesive resin and / or biodegradable polyethylene terephthalate resin used in the formation of the skin and core may contain 0.5 to 3.0 weight percent of a biodegradable agent. The biodegradable agent may contain one or more selected from aliphatic esters, aromatic esters, and monosaccharides (polylactide). If the content of the biodegradable agent is less than 0.5 weight percent, the biodegradability will be reduced. If it is greater than 3.0 weight percent, the cross-section formability will be reduced during spinning, resulting in a problem of reduced spinning operability. In addition, excessive addition of a biodegradable agent will reduce heat resistance and thermal bonding performance.

[0029] Furthermore, the core of the core-sheath composite fiber can be composed of a high-melting-point biodegradable polyester resin. In this case, although the high-melting-point biodegradable polyester resin in the core has a lower melting point than ordinary high-melting-point PET due to the addition of a biodegradable agent, the melting point can still be above 220°C. In a preferred embodiment, high-melting-point biodegradable polyethylene terephthalate (PET) can be used. When the melting point of the high-melting-point biodegradable polyester resin is above 220°C, the core stably maintains the fiber shape during thermal fusion, thereby improving the pore formation. Moreover, the difference between the melting point or softening point of the sheath and the melting point of the core needs to be above 80°C. In this case, if the melting point difference is less than 80°C, problems of reduced pore formation and reduced air permeability will occur when the non-woven fabric is prepared by thermal fusion.

[0030] Moreover, the weight ratio of the sheath to the core of the sheath-core composite fiber may be 6.0:4.0 to 4.5:5.5, and preferably, the weight ratio of the sheath to the core may be 5.5:4.5 to 4.8:5.2. In this case, if the weight ratio of the core is less than 4.0 weight ratio, the pore forming property of the dry nonwoven fabric may be reduced, and if it is greater than 5.5 weight ratio, the amount of low melting point PET constituting the sheath in the composite fiber may be relatively small, resulting in insufficient thermal fusion property and insufficient morphological stability. That is, this can provide the filter support with an appropriate thickness and air permeability and further improve the morphological stability.

[0031] Furthermore, in the present invention, the biodegradable thermal bonding composite fiber does not use a side-by-side thermal bonding composite fiber because if the first component composed of a low melting point polyester resin and the second component composed of a high melting point PET are used as side-by-side thermal bonding composite fibers, the first component and the second component will be spirally entangled due to the difference in viscosity, resulting in poor morphological stability, and thus are not suitable for use as a filter support.

[0032] The air permeability of the thermally fused biodegradable filter support body, which includes a laminate of a dry-laid nonwoven fabric prepared using the biodegradable thermally bonded composite fiber described above in a single layer or multiple layers, can be 200 to 600 ccs (cm 3 / cm 2 / sec), more preferably, it can be 250-500ccs, and even more preferably, it can be 300-450ccs. The heat-fused filter support used together with the dust collector in the composite filter aluminum material focuses on air permeability. If the air permeability is too large, the poor bending operability will be caused due to the insufficient morphological stability of the filter support. If the air permeability is too small, the filter support as a dust collector will become an obstacle to increased energy costs due to increased pressure loss. Therefore, when the air permeability meets 200-600ccs, it can be used as a filter support for filter media that has good morphological stability and bending operability and saves energy costs.

[0033] On the other hand, in order to design in a manner having the above-mentioned air permeability, the average fineness of the thermally bonded composite fibers constituting the dry nonwoven fabric is 6 to 15 deniers (de, denier), preferably, the average fineness is 10 to 15de. When such a fineness range is met, it is beneficial to achieve the target level of morphological stability, thickness level, pore size, pores, air permeability, etc. If the average fineness of the composite fiber is less than 6de, it will be difficult to achieve the target physical properties due to problems such as increased pressure loss of the filter support due to too small air permeability and increased energy consumption costs. If the average fineness of the composite fiber is greater than 15de, although the air permeability is increased, it will be difficult to achieve the target physical properties of the present invention due to problems such as reduced filtration efficiency due to excessively large pores of the nonwoven fabric or poor bending operability due to increased thickness of the filter support.

[0034] Furthermore, the average fiber length of the thermally bonded composite fibers may be 38 to 64 mm, preferably, the average fiber length may be 38 to 51 mm, which will be more conducive to achieving the purpose of the present invention.

[0035] Furthermore, according to one embodiment of the present invention, the weight of the thermally fused biodegradable filter support (or dry-laid nonwoven fabric) may be 40 to 120 g / m 2 , preferably, it can be 50 to 100 g / m 2 More preferably, it can be 60 to 90 g / m 2 If the weight is less than 40g / m 2 If the weight is greater than 120g / m 2 If the thickness is increased, the air permeability will decrease, which will increase the pressure loss, leading to increased energy costs and other obstacles, making the cost reduction effect of lightweighting the filter support body less effective.

[0036] In addition, the thickness of the heat-fused biodegradable filter support of one embodiment of the present invention can be 0.2-0.8 mm, preferably 0.25-0.6 mm, and more preferably 0.3-0.5 mm. If the thickness is less than 0.2 mm, it will lead to poor morphological stability, and then the dust collection amount will be reduced due to insufficient space for collecting dust, thereby shortening the life of the filter. If the thickness is greater than 0.8 mm, the pressure loss will increase due to the decrease in air permeability. Therefore, it is better to use a dry non-woven fabric with a thickness in the above range as the heat-fused filter support.

[0037] In addition, the tensile strength in the MD direction of the heat-fused biodegradable filter support of one embodiment of the present invention may be 6kgf / 5cm or more, preferably 8kgf / 5cm or more, and more preferably 10kgf / 5cm or more. If the tensile strength in the MD direction is less than 6kgf / 5cm, the shape stability will be poor, and the poor bending operability during bending will have an adverse effect on the filtration efficiency and pressure loss. Therefore, it is preferred to use a dry nonwoven fabric having a tensile strength in the MD direction within the above range as the heat-fused filter support.

[0038] Furthermore, the tensile strength retention rate of the biodegradable filter support determined by the following formula 1 according to one embodiment of the present invention can be 90% or more. If the tensile strength retention rate in the MD direction is less than 90%, the filter's morphological stability and bending operability are poor due to the decrease in tensile strength after 6 months of use under the following temperature and humidity conditions. Therefore, it can be seen that the physical properties of the filter support should be maintained during the normal use period and conditions of the filter. Moreover, the tensile strength retention rate is similar to that of the non-degradable filter support, which shows that there is no problem in maintaining biodegradability while serving as a filter support.

[0039] Formula 1

[0040] Tensile strength retention rate (%) = 100% - [(A-B) / A] × 100%

[0041] Wherein, A is the tensile strength in the machine direction (MD) of the initial biodegradable filter support, and B is the tensile strength in the MD direction measured after the initial biodegradable filter support is placed at 25 (±10)°C and a relative humidity of 55 (±15)% for 180 days.

[0042] The present invention is a composite filter material suitable for an air filter, comprising the dry heat-fused biodegradable filter support body described above and a dust collecting member arranged on one side of the heat-fused biodegradable filter support body.

[0043] Hereinafter, the present invention will be described in detail by way of examples.

[0044] However, the following examples are only for illustrating the present invention, and the contents of the present invention are not limited to the following examples.

[0045] Example

[0046] Example 1: Preparation of thermally fused biodegradable filter support (dry-laid nonwoven fabric)

[0047] As biodegradable thermal bonding composite fibers (core-sheath type composite fibers having a sheath-to-core weight ratio of 5:5), single fibers having an average fineness of 10 de and an average fiber length of 51 mm were prepared.

[0048] The skin portion is composed of a biodegradable polyester thermal adhesive resin (melting point 110° C.) as a low melting point polyester resin, and the biodegradable polyester thermal adhesive resin contains terephthalic acid as an acid component and a polymer resin as a diol component. The diol component contains 40 mol % of 2-methyl-1,3-propanediol, 1.0 mol % of the 2-methyl-1,3-pentanediol, and the remainder of 100 mol % of ethylene glycol.

[0049] Furthermore, the biodegradable polyester thermal adhesive resin contains 1.5 weight percent of polylactic acid as a biodegradation agent.

[0050] The core is made of biodegradable PET resin (melting point 230-260° C.), and the biodegradable PET resin constituting the core contains 1.5 weight percent of polylactic acid as a biodegradation agent.

[0051] Next, the core-sheath biodegradable thermal bonding composite fiber is sequentially passed through Figure 1 The material supply section, material mixing section, hopper section, carding section, web laying section, drafting section, thermal fusion bonding section, and winding section as shown in the nonwoven fabric preparation process are used to prepare a dry nonwoven fabric. In this case, the thermal fusion bonding section is calendered at 170°C and 4kg / cm 2 The dry-laid nonwoven fabric (weight 70 g / m2) having the properties shown in Table 1 was thermally fused by pressure. 2 ) is prepared as a heat-fused biodegradable filter support.

[0052] More specifically, a raw yarn is supplied through a material supply section 100 for use as a raw yarn, the entangled raw yarns supplied from the material supply section 100 are mixed with each other through a material mixing section, the entangled raw yarns mixed by the material mixing section 200 are separated by a hopper section 300, the raw yarns separated by the hopper section 300 are unfolded to a specified thickness by a combing section 400 to form a film form, a single-layer non-woven fabric layer supplied from the combing section 400 is moved left and right by a web laying section 500 to be stacked into a plurality of layers to form a non-woven fabric layer of a specified thickness, the non-woven fabric layer supplied from the web laying section 500 is stretched and transferred by a drafting section 600, the non-woven fabric layer stretched and transferred in the drafting section 600 is combined using heat and pressure by a thermal fusion bonding section 700, and the non-woven fabric combined by the thermal fusion bonding section 700 is wound by a winding section 800 to prepare a dry non-woven fabric.

[0053] Comparative Example 1

[0054] A dry-laid nonwoven fabric is prepared in the same manner as in Example 1, with a weight ratio of the sheath to the core of a non-biodegradable common polyester heat-fused composite fiber of 5:5, and fibers with a fineness of 10 de and a fiber length of 51 mm are used as the raw yarn to prepare the dry-laid nonwoven fabric as a heat-fused filter support.

[0055] Example 2 to Example 5 and Comparative Examples 2 to Comparative Examples 5

[0056] The preparation was carried out in the same manner as in Example 1, and the heat-fused biodegradable filter support shown in Table 1 was prepared by changing the fineness of the heat-bonded composite fiber, the grammage, thickness, air permeability, tensile strength, etc. of the biodegradable filter support.

[0057] Experimental Example 1

[0058] The following physical properties of the heat-fused biodegradable filter supports prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were evaluated. The results are shown in Table 1 below.

[0059] (1) Weight

[0060] Use a common weight scale to measure the gram weight of the filter support. Cut the filter support into 50×50cm in size at three points, including the center and the left and right middle positions based on the center. Measure the weight and find the average value, and convert it into 1m 2 ) weight (g) and then weight (g / m 2 ) to indicate.

[0061] (2) Thickness

[0062] The thickness of the prepared filter support was measured using a thickness meter (MODEL H, PEACOCK, Japan) The thickness was measured at three points, namely, the center of the nonwoven fabric and the middle position on the left and right sides of the center, and the average value was calculated.

[0063] (3) Air permeability

[0064] The air permeability of the prepared filter support was measured using an air permeability meter (MODEL FX-3300, TEXTEST). The air permeability was measured at three points, including the center of the nonwoven fabric and the middle position on the left and right sides of the center, and the average value was obtained. The measurement was performed at a measurement pressure of 125 Pa and expressed in ccs.

[0065] (4) Tensile strength

[0066] The tensile strength in the MD direction of the prepared filter support was measured according to KS K ISO 9073-3. The clamp spacing of the tensile strength tester was set to 200 mm, and the two ends of the test piece in the MD direction were held between them. The test piece was flatly unfolded and held in such a way that the load was at the zero point of the curve, and after recording the load-tensile curve of each test piece at a constant tensile speed of 100 mm / min, the maximum breaking strength was measured in kg / 5 cm. In addition, the tensile strength in the MD direction was measured after being placed under temperature and humidity conditions of (25±10)°C and (55±15)% relative humidity (RH) for 6 months (180 days) to confirm the change in tensile strength over time.

[0067] (5) Tensile strength retention rate

[0068] The tensile strength retention rate was measured and calculated by the following formula 1.

[0069] Formula 1

[0070] Tensile strength retention rate (%) = 100% - [(A-B) / A] × 100%

[0071] Wherein, A is the tensile strength in the MD direction of the initial biodegradable filter support, and B is the tensile strength in the MD direction measured after the initial biodegradable filter support is placed at 25 (± 10) °C and a relative humidity of 55 (± 15)% for 180 days.

[0072] (6) Comprehensive evaluation

[0073] The physical properties of the biodegradable and general filter supports prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were measured and evaluated. The physical property evaluation results showed that the thickness was 0.2 to 0.8 mm, the gram weight was 40 to 120 g / m 2 The cases with air permeability of 200 to 600 ccs, tensile strength of 6 kgf / 5 cm or more, and tensile strength retention of 90% or more were judged as (○), and the other cases were judged as poor (×).

[0074] Table 1

[0075]

[0076] From Table 1, it can be seen that in the case of Comparative Example 2 and Comparative Example 3, where the biodegradable thermal bonding composite fiber has a fineness of 4de and 2de, the air permeability is reduced due to the small fiber diameter, and finally the filter pressure loss increases, making it unsuitable as a filter support. In addition, it can be seen that in the case of Comparative Example 4, the air permeability is reduced due to the reduction in thickness and excessive thermal fusion, and in the case of Comparative Example 5, the porosity is increased due to the fluffy structure, which increases the air permeability, makes the shape stability of the support poor, and reduces the tensile strength, making it unsuitable as a filter support.

[0077] Moreover, compared with Comparative Example 1, which is a conventional filter support prepared using conventional polyester thermally bonded composite fibers of 10 deg, it can be confirmed that the physical properties of the biodegradable filter support of Example 1 prepared using the same 10 deg of biodegradable thermally bonded composite fibers show values ​​similar to those of the conventional filter support.

[0078] In addition, the tensile strength used as a substitute for the morphological stability and bending operability also showed similar values. When the tensile strength was 6 kgf / 5 cm or more, the bending operability also showed good results, indicating that a biodegradable filter support that can replace the existing thermal bonding composite fiber can be prepared. In addition, after 6 months (180 days), the MD direction tensile strength retention rate was also 90% or more, showing a value similar to that of the existing Comparative Example 1, etc., indicating that a biodegradable filter support with excellent physical properties as a filter support can be prepared.

[0079] Experimental Example 2: Evaluation of Composite Biodegradability

[0080] The composite biodegradability of the dry-laid nonwoven fabrics (biodegradable filter supports) prepared in Example 1, Example 3 and Comparative Example 1 was evaluated and is shown in Table 2 below.

[0081] (1) Evaluation of composite biodegradability

[0082] The biodegradability and composite biodegradability of common filter supports were measured according to ISO 21701. ISO 21701 pre-treats the sample under the conditions of "temperature 90°C*humidity 95%RH" (384 hours) to simulate the time point when fiber products are discarded after use, and then measures the amount of CO2 generated during biodegradation after 180 days under the conditions of ISO 14855-1, which is an existing biodegradation analysis method, to evaluate the biodegradability.

[0083] Table 2

[0084] Filter support Composite biodegradability (%) Example 1 61.8 Example 3 62.1 Comparative Example 1 4.6

[0085] The composite biodegradability evaluation results of the filter supports of Example 1, Example 3 and Comparative Example 1 can be confirmed in Table 2, and the biodegradability of the biodegradable filter supports of Example 1 and Example 3 prepared using the biodegradable thermally bonded composite fiber can be confirmed. In addition, from the results of Tables 1 and 2, it can be seen that an environmentally friendly biodegradable filter support can be prepared that maintains physical properties under the conditions of use as a filter support and is biodegraded in a soil landfill when discarded after use.

[0086] Preparation Examples 1 to 2 and Comparative Preparation Example 1: Preparation of composite filter material for air filter

[0087] The biodegradable filter supports of Example 1 and Example 3 and the filter support of Comparative Example 1 were used to prepare composite filter materials for air purifiers. In this case, the filter dust collector used a melt-blown nonwoven filter fabric showing E-12 grade performance, and the filter dust collector was combined with the biodegradable filter support (or filter support) by a thermal fusion bonding method. After preparing the composite filter material, it was bent by a common method to prepare a curved air filter composite filter material, and then processed to prepare an air filter composite filter material with a filter size of 340 mm (H) * 380 mm (W) * 35 mm (D), thereby implementing Preparation Examples 1 to 2 and Comparative Preparation Example 1, respectively.

[0088] Experimental Example 3: Determination of the efficiency of composite filter media for air filters

[0089] The filtration efficiency (%) and pressure loss (mmH2O) of the composite filter materials of the air filters of Preparation Example 1 (Example 1), Preparation Example 2 (Example 3) and Comparative Preparation Example 1 (Comparative Example 1) were evaluated by the following method. The results are shown in Table 3 below.

[0090] (1) Filtration efficiency and pressure loss measurement method

[0091] The filtration efficiency (%) and pressure loss (mmH2O) are evaluated according to the KS C 9325 method. In this case, the test is carried out under the following conditions: the wind tunnel length of the equipment used is about 8M, the wind tunnel cross-sectional area is 600mm*600mm, the temperature and humidity conditions are (25±10)℃, (55±15)%RH, and the air supply volume is 540m 3 In this case, the differential pressure gauge used was FLUKE 400 mmH2O (FLUKE, USA), and the particle counter was GRIMM 11-A (GRIMM, Germany).

[0092] Table 3

[0093]

[0094]

[0095] It can be confirmed in Table 3 that the results of evaluating the filtration efficiency and pressure loss of the air filter assemblies prepared using the filter supports of Example 1, Example 3 and Comparative Example 1 show that the filtration efficiency and pressure loss values ​​of the air filter assemblies of Preparation Examples 1 and Preparation Examples 2 are similar to and show good values ​​for the air filter assembly of Comparative Preparation Example 1 prepared using Comparative Example 1 which is an existing non-degradable ordinary filter support, thereby confirming that the biodegradable filter support of the present invention can replace the existing ordinary filter support.

Claims

1. A heat-fused biodegradable filter support for air filter material, which is a dry-laid nonwoven fabric formed by a single layer or multiple layers, characterized in that: The dry-laid nonwoven fabric comprises polyester biodegradable thermal bonding composite fibers with a fiber length of 38 to 64 mm and a fineness of 6 to 15 deniers. The dry nonwoven fabric has a gram weight of 40 to 120 g / m 2 , thickness is 0.2~0.8mm.

2. The heat-fused biodegradable filter support for air filter media according to claim 1, characterized in that: The dry-laid nonwoven fabric is formed by thermally fusing polyester biodegradable thermal bonding composite fibers.

3. The heat-fused biodegradable filter support for air filter media according to claim 1, characterized in that: The polyester biodegradable thermal bonding composite fiber comprises a core-sheath type biodegradable thermal bonding composite fiber, The sheath-core biodegradable thermal bonding composite fiber comprises: a core comprising a biodegradable polyester resin; and a sheath portion comprising a biodegradable polyester thermal adhesive resin having a lower melting point or softening point than the core portion, The weight ratio of the skin part to the core part is 6.0:4.0 to 4.5:5.

5.

4. The heat-fused biodegradable filter support for air filter media according to claim 1, characterized in that: The air permeability of the biodegradable filter support is 200 to 600 ccs.

5. The heat-fused biodegradable filter support for air filter media according to claim 1, characterized in that: The biodegradable filter support has a tensile strength of 6 kgf / 5 cm or more.

6. The heat-fused biodegradable filter support for air filter media according to claim 1, characterized in that: The tensile strength retention rate of the biodegradable filter support determined by the following formula 1 is 90% or more, Formula 1: Tensile strength retention rate (%) = 100% - [(A-B) / A] × 100%, Wherein, A is the machine direction tensile strength of the initial biodegradable filter support, and B is the machine direction tensile strength measured after the initial biodegradable filter support is placed at 25±10° C. and 55±15% relative humidity for 180 days.

7. A composite filter material for an air filter, characterized in that: include: The heat-fused biodegradable filter support according to any one of claims 1 to 6; as well as The dust collecting member is arranged on one side of the biodegradable filter support.

Citation Information

Patent Citations

  • Base material of air filter

    JP2003126628A

  • Environment friendly non-woven for engine filter, method for manufacturing the same and engine filter comprising the same

    KR101180374B1

  • Filter substrate of dry laid thermal bonding nonwoven

    KR102011071B1

  • Non-woven fabrics and production method thereof, production apparatus used for the production method, cushion materials, filters, non-woven fabric structures using the same and non-woven fabric suitable to cushion materials

    US20050020171A1